2021
DOI: 10.4018/ijegr.2021040101
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Implementing E-Government in Health Insurance Administration

Abstract: Health insurance administration (HIA), a governmental institution that provides health insurance services for citizens in Jordan, is investing in an electronic health insurance administration (EHIA) system. This paper aims to explore the main factors influencing users' intention to adopt EHIA in Jordan, where little research focused on such systems. Using a quantitative approach, a sample of 315 citizens was utilized, and an instrument of 30 items was used. Findings revealed that perceived ease of use, perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Sixteen hypotheses were tested to determine the relationship between users' satisfaction with E-government service usage and the following factors: information quality, system quality, service quality, trust, usefulness, perceived ease of use, attitude towards use, behaviour intention to use E-government services, and users' satisfaction with E-government service usage (see Figure 1). e results indicated a certain trust in the Internet and trust in government, and perceived ease of the use, usefulness, information systems background, and social power were all significant predictors of citizens' intention to adopt E-services, which is consistent with [75,76]. Based on the explored concepts discovered from the aforementioned hypotheses, in Malaysia, the E-government users reported that their satisfaction would be directly correlated with the quality of system, information, and services.…”
Section: Discussion and Eoretical And Practical Contributionssupporting
confidence: 55%
“…Sixteen hypotheses were tested to determine the relationship between users' satisfaction with E-government service usage and the following factors: information quality, system quality, service quality, trust, usefulness, perceived ease of use, attitude towards use, behaviour intention to use E-government services, and users' satisfaction with E-government service usage (see Figure 1). e results indicated a certain trust in the Internet and trust in government, and perceived ease of the use, usefulness, information systems background, and social power were all significant predictors of citizens' intention to adopt E-services, which is consistent with [75,76]. Based on the explored concepts discovered from the aforementioned hypotheses, in Malaysia, the E-government users reported that their satisfaction would be directly correlated with the quality of system, information, and services.…”
Section: Discussion and Eoretical And Practical Contributionssupporting
confidence: 55%
“…E-learning is also vital for the management of knowledge (KM) business since they assist all knowledge management phases socialization, outsourcing, gathering, and assimilation. The usage of e-learning and its success can enhance organizational capacity (Hammouri et al, 2021). The review may also demonstrate that if e-learning is easy for students to utilize, it will also be of great benefit to their use and acceptance.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Talents are a distinct and subjective ability, but it is characterized by privacy, and talents differ from the hobby, as the talents exist in the individual since his inception, but they are crystallized through training and the provision of knowledge. Talent plays a positive role in a person's life, as it helps him achieve himself (Bersin, 2006) As for the term on line human resources management, it was coined by (David Watkins) in (1998) when he published his article entitled "The War for Talent", after which a group of researchers later published a book entitled (The War for Talent), and this management emerged at the beginning to improve the recruitment process and develop the skills necessary to meet the current organizational needs, and over time it developed along with its increasing responsibilities, and was integrated with the goals and strategies of the organization (Aljanabi et al, 2020;Hammouri et al, 2021). Many definitions of on-line human resources management have emerged, and the most important of these definitions are the following (Aljanabi et al, 2020):…”
Section: Digital Human Resources Conceptmentioning
confidence: 99%